BALF metagenomic next-generation sequencing for the diagnosis of pulmonary mycobacterial infection in persons with HIV: a retrospective, diagnostic accuracy study - Miao, Mengjiao; Ma, Chenyu; Yang, Jinjin; Yang, Xihong; Liu, Ziyao; Liu, Anni; Qian, Zheng; Ge, You; Chen, Yaling; Yin, Guoping; Hu, Zhiliang (Frontiers in Microbiology, 2025)
Severely immunocompromised persons with HIV (PWH) are vulnerable to pulmonary mycobacterial infections (MBI), including Mycobacterium tuberculosis (MTB) and non-tuberculous mycobacteria (NTM). This study aimed to assess the effectiveness of metagenomic next-generation sequencing (mNGS) of bronchoalveolar lavage fluid (BALF) in aiding the diagnosis of pulmonary mycobacterial infections in PWH. This study encompassed 146 hospitalized PWH who had a CD4+ T cell count of less than 200 cells/μL. We employed BALF mNGS to pinpoint the causative pathogens of pulmonary infections, with particular focus on pulmonary mycobacterial infections. We evaluated the diagnostic performance of BALF mNGS, and interpreted its clinical significance in detecting mixed infections as appropriate. The median CD4+ T cell count of the participants was 22.5 (IQR: 7.0–63.0) cells/uL. BALF mNGS analysis of 146 severely immunocompromised PWH identified Mycobacterium tuberculosis (13.0%) and M. avium complex (7.5%) as the predominant mycobacterial species, with 9.3% (4/43) of mycobacterial infections showing mixed speciation including TB-NTM co-infections or interspecies NTM coinfections. Furthermore, mNGS demonstrated 78.8% sensitivity (95% CI: 62.2%−89.3%) for proven mycobacterial infections, outperforming conventional culture (68.4% vs. 42.1%, P < 0.01), though missing 7 proven MBI cases. Finally, among 158 co-detected pathogens, Pneumocystis jirovecii (67.1%) and cytomegalovirus (63.0%) were most prevalent, demonstrating co-occurrence rates of 53.5% and 55.8%, respectively in mycobacterial-infected patients. These rates were elevated to 81.2% (P. jirovecii) and 65.3% (CMV) in the subset of 101 patients with CD4+ counts <50 cells/μL. The presence of atypical clinical presentations, along with the coexistence of multiple opportunistic pathogens in BALF, complicates the management of pulmonary MBI in PWH. In this context, mNGS has emerged as a highly promising microbiological test that could revolutionize the management of pulmonary MBI in PWH.